Neuropathic Pain Screening: Construct Validity in Patients With Sickle Cell Disease. (February 2020) - Powell-Roach, Keesha; Yao, Yingwei; Ezenwa, Miriam O.; Schlaeger, Judith M.; Suarez, Marie L.; Molokie, Robert E.; Wang, Zaijie Jim; Wilkie, Diana J.
Individuals with pain from sickle cell disease (SCD) are often treated for nociceptive pain, but recent findings indicate they may also have neuropathic pain. PAIN Report It, a computerized version of the McGill Pain Questionnaire, provides a potential subscale that is the summed number of selected neuropathic pain quality words (PR-NNP), but it lacks construct validity. The study purpose was to ascertain PR-NNP construct validity in adults with SCD and chronic pain. In an outpatient setting, 186 participants completed the PAIN Report It, Neuropathic Pain Symptom Inventory (NPSI), and Leeds Assessment for Neuropathic Symptoms and Signs (S-LANSS). PR-NNP was moderately correlated with NPSI ( r = .33, p < .001) and S-LANSS ( r = .40, p < .001). Regression analysis indicated that PR-NNP and pain intensity, but not a nociceptive pain subscale, were significant predictors of NPSI and S-LANSS. Findings support construct validity of PR-NNP, which may be useful as a screening tool for neuropathic pain in patients with SCD.